Electronic phase transitions in ultrathin magnetite films. (8th July 2015) - Bernal-Villamil, I; Gallego, S
Abstract: Magnetite (Fe3 O4 ) shows singular electronic and magnetic properties, resulting from complex electron–electron and electron–phonon interactions that involve the interplay of charge, orbital and spin degrees of freedom. The Verwey transition is a manifestation of these interactions, with a puzzling connection between the low temperature charge ordered state and the dynamic charge fluctuations still present above the transition temperature. Here we explore how these rich physical phenomena are affected by thin film geometries, particularly focusing on the ultimate size limit defined by thicknesses below the minimum bulk unit cell. On one hand, we address the influence of extended defects, such as surfaces or antiphase domains, on the novel features exhibited by thin films. On the other, we try to isolate the effect of the reduced thickness on the electronic and magnetic properties. We will show that a distinct phase diagram and novel charge distributions emerge under reduced dimensions, while holding the local high magnetic moments. Altogether, thin film geometries offer unique possibilities to understand the complex interplay of short- and long-range orders in the Verwey transition. Furthermore, they arise as interesting candidates for the exploitation of the rich physics of magnetite in devices that demand nanoscale geometries, additionally offering novel functionalities based on their distinct properties with respect to the bulk form.